Influence of starch acetylation on selected rheological properties of pastes. Issue 3 (19th September 2013) - Żmudziński, Daniel; Ptaszek, Anna; Grzesik, Mirosław; Kruk, Joanna; Kaczmarczyk, Kacper; Liszka‐Skoczylas, Marta
Abstract Selected rheological properties of acetylated starch pastes of different amylose content were discussed in the study. The rheological studies were carried out immediately after the preparation of the pastes as well as after 1 and 7 days of storage. For the paste of acetylated potato starch (P‐A), a phenomenon of oscillatory changes of viscosity with time was observed. The pastes of the acetylated amylostarch (AMY‐A) and acetylated waxy potato starch (AP‐A) exhibited the phenomenon of thixotropy. Based on the flow curves, the distribution of the time constants of the exponential rheological equation of state has been determined. They served to describe the contributions forming rheological properties. It has been noticed that during shear the phenomenon of the energy dissipation is predominant in AMY‐A (rheological characteristic time of 0.3 s) and AP‐A, whereas the elastic contributions are specific for the paste of acetylated potato starch (rheological characteristic time of 10−6 s). In order to describe the structural changes of AMY‐A and AP‐A pastes during flow, i.e. for the systems exhibiting frictional properties, the Cheng and Evans viscous structural theory has been applied. The rheological properties were then interpreted in light of the results of chromatographic and osmometric analyses.